Malignant Lymphomas of Non-Hodgkin Type in the Annals of Stomatology Clinic in Hradec Králové 1998-2008 - V. Nováková; D. Belada; J. Laco; P. Kašparová; M. Nová; R. Slezák (Czech Dental Chamber, 2011)
Introduction: Malignant lymphomas of non-Hodgkin type (NHL) are the second most frequent malignant tumors in the head and neck area, although they represent only 2.2% of malignancies in this region and 2-3% of all NHL. Objective: the aim of the work was to analyze the problem of NHL from the standpoint of a stomatology clinical workplace. Methods: The review of available literature was at first devoted to analyze the problems in general. The actual retrospective study included 24 patients, who were diagnosed NHL in the period of January 1st 1998 to December 31st 2008 at our workplace. The follow up study concerned 22 individuals, while 13 of them had been treated by chemotherapy, 7 by immunotherapy, one by a combination of radiotherapy and chemotherapy and one by surgery. The median of observation was 52 months. Results: In 7 cases there was a nodal affection, 17 cases suffered from extranodal NHL (ENHL). In the ENHL group we encountered five times the affection of great salivary glands; the affection of alveolar process, buccal or vestibular mucosa and the buccal wall were represented evenly (three cases in all localizations); the roof of the mouth was affected in two cases and the tongue once. On the whole, 91.7% of the lymphomas were of B-cell origin. In the group of nodal lymphomas, the follicular lymphoma was most frequent (6 cases), in the ENHL group the follicular lymphoma was also most frequent (6 cases), followed by diffuse large cell B lymphoma (4 cases) and extranodal lymphoma from marginal zone (two cases). At the time of end of the observation (January 1st 2010), 71.4% patients of those we were in touch still lived. Conclusion: Early and rapid diagnosis of NHL can principally influence the prognosis of the disease quo ad vitam and it is therefore necessary to have this kind of malignant disease in mind even in the orofacial area.